SOCIOLINGUISTIC IMPLICATIONS OF ONLINE EFL LEARNING: AN EMPIRICAL STUDY OF LANGUAGE USE AND INTERACTION IN TEACHER EDUCATION - Maida Maqsood; Dr. Shehla Sheikh; Sultan Akbar Shah; Zeeshan Haider; Saba Gul; Aleeza Gul (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
This empirical study delves into the sociolinguistic implications of online English as a Foreign Language (EFL) learning, with a particular focus on the language use and interaction dynamics in teacher education. To conduct this investigation, qualitative research methods were employed, encompassing semi-structured interviews with a diverse group of EFL learners and the observation and analysis of real-time language interactions within virtual lessons. The results of the study shed light on the multifaceted language practices of online EFL learners, influenced by factors such as the virtual environment, language proficiency levels, and teacher-student interactions. Instances of code-switching, language negotiation, and emerging language norms emerged within the digital language learning context. The study underscores the significance of technology-enhanced language learning in shaping sociolinguistic dynamics and highlights the need to cultivate a supportive virtual classroom environment that encourages effective language communication and embraces linguistic diversity. By contributing valuable insights into the implications of technology integration in EFL education, this research offers meaningful guidance to educators and policymakers seeking to optimize language learning experiences in online settings.